Using Natural Dye as Sensitizers in DSSC - Prasad Tripathy, Hara; Pattanai, Priyabrata; Kumar Kamilla, Susanta (International Journal of Psychosocial Rehabilitation, 2025)
The “dye-sensitized solar cell (DSSC)” uses Roselle flower as a sensitizer. It is also known as Hibiscus Sabdariffa L. The ethanol (E) and distilled water (DI) is used for extracting solvent at 30° temperature at 37Hz by ‘degas’ mode for a time period of 30 minutes in ultrasonic cleaner. Fabricating titanium dioxide (TiO2) was done by the method of doctor blade on ITO glass. “Evolution 201 UV-Vis Spectrophotometer” was used for absorbing Roselle dye spectra in various extract solvent. In the extract dye, the active functional group was identified by “Fourier-Transform Infrared (FTIR)”. The element in TiO2 thin film and surface morphology are characterized by “field emission scanning electron microscopy (FESEM)” and “energy-dispersive spectroscopy (EDS)”.